Immune Response to Burn Injury: Hyperinflammation and Immunosuppression - Septin Mauludiyana; Aryati; Yoes Prijatna Dachlan; Iswinarno Doso Saputro; Muhaimin Rifa’i (Indian Journal of Forensic Medicine & Toxicology, 2021)
Burn is an injury to the skin or other tissue. Mostly, it caused by contacting with hot liquids, solids, and flames. The important thing that should be consider in burn incident is the severity of burn and it based on the depth and area of the burn injury. The severity of burns will cause differences of pathophysiological responses. This was a literature review study. Various articles were collected from online database including reports, journals, and published in the last 10 years. The articles were from the scholar journals. The systemic inflammatory response in severe level of burns was not given good response to disappear of lesion burn and initiating tissue repair. Moreover, it was given an organ failure to the patient. The body responded to this incident by releasing antiinflammatory mediators. This response is very strong and prolonged, so it caused immunosuppression and increase the risk of secondary infection to the patients. Burns affects the patient’s immune system. The ratio between pro and antiinflammatory mediators are determining the patient’s subsequent status.